Heat Transfer Analysis Of Carbon Nanofluids Under Stretch-Induced Flow (International Journal of Food and Nutritional Sciences, 2022)
In this paper we have considered Two-dimensional flow and heat transfer of carbon-nano fluids which contain SWCNT and MWCNT. The governing equations of flow and heat transfer partial differential equations are transferred into ordinary differential equations, which are solved numerically. The effects of physical parameters on flow and heat transfer are analyzed with aid of graphs. The wall temperature gradient and skin friction quantities are numerically calculated and tabulated. Our results are in good agreement with earlier studies for some limitations cases.